ANALISIS PENGARUH STRES KERJA, KOMPENSASI, DAN EMPLOYEE ENGAGEMENT TERHADAP KINERJA PEGAWAI (Studi pada Pegawai PDAM Tirta Moedal Kota Semarang) - Widyastuti, Nova; Rahardja, Edy (Diponegoro Journal of Management, 2018)
Organizational performance is good if the performance of the employees is also good. Good or bad employee performance can be influenced by various factors. Therefore, the purpose of this research is to find out how big the influence of job stress, compensation, and employee engagement on the employee performance at Perusahaan Daerah Air Minum (PDAM) Kota Semarang based on organizational performance data for 2 consecutive years.This research used quantitative approach with the population of employee PDAM Tirta  Moedal  Kota  Semarang  amounting  to  479  people  with  sample  of  the  research counted 100 people using purposive sampling technique. The processed of data by using the help of SPSS 23.0 version, and the method used in analyzing data in this research is linear regression analysis.Based on the results of the study, it was found that: (1) work stress had a negative and significant effect on employee performance; (2) compensation has a positive and unsignificant  effect  on  employee  performance;  and  (3)  employee  engagement  has  a positive and significant effect on employee performance.